Social representations of nursing students on the rights of health users - Fernanda Duarte da Silva; Thémistoklis Apostolidis; Márcia de Assunção Ferreira (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To identify the social representations of undergraduate nursing students in the third and eighth term of the course on the rights of health users. Methods: Qualitative research using the framework of the structural approach to the Theory of Social Representations. A total of 92 students participated. The free evocation technique was used and data was processed in the EVOC software. Results: In the social representations of the third term students, words related to health policies were not observed, but there is an evaluation of the service in the institutions. Among the eighth-grade students, the concepts that support the policies of the Unified Health System are evident. Final considerations: There is a consolidation of the students' knowledge throughout the course, with a more elaborated knowledge about the users' right, supported by principles of the SUS. Undergraduate education is an important space for discussing the construction and exercise of citizenship, including the right to health.